A Schiff base platform: structures, sensing of Zn(ii) and PPi in aqueous medium and anticancer activity. Issue 29 (12th July 2017) - Naskar, Barnali; Modak, Ritwik; Maiti, Dilip K.; Drew, Michael G. B.; Bauzá, Antonio; Frontera, Antonio; Das Mukhopadhyay, Chitrangada; Mishra, Snehasis; Das Saha, Krishna; Goswami, Sanchita
Abstract : A Schiff base platform was explored to present structural aspects of its Zn(ii ) and Cd(ii ) coordination compounds, sensing behavior towards Zn(ii ) and PPi in aqueous medium and anticancer activity. Abstract : A reaction of N 1, N 3 -bis(3-methoxysalicylidene) diethylenetriamine (H2 Vd ) and Zn(NO3 )2 ·6H2 O, ZnBr2, ZnI2 and Cd(NO3 )2 ·4H2 O in a methanol solution led to zinc and cadmium complexes of different nuclearities, [Zn2 (Vd·H)2 (X)2 ]·CH3 OH (X = NO3, Br, I) [1a, 1b and1c ] and Cd3 (Vd)2 (NO3 )2 (2 ). In1(a–c), twoH2 Vd ligands bridge the two metal centers whereas in2, they provide sideways support to two terminal Cd 2+ ions, providing an all-oxygen envelope to the central Cd 2+ ion. All four compounds were characterized by elemental analysis, FT-IR spectroscopy and single crystal X-ray diffraction analysis. Complexes1(a–c) exhibit dinuclear structures, whereas2 exhibits a nearly linear trinuclear structure. The structural differences among these complexes are attributable to various coordination modes and flexible configurations of theH2 Vd ligand. The ligandH2 Vd is an excellent probe for sensing Zn 2+ in solution, whereas complexes1(a–c) are able to selectively detect pyrophosphate (PPi) in aqueous medium. The structure of the pyrophosphate (PPi) complex has been proposed using DFT calculations and the selectivity is due to the unique ability of this anion to simultaneously coordinate to both the Zn metal centers. The anticancer activity of complexes1(a–c) was also explored.